Facilitated Deferred Transmmission a Risk to Public Health of Globalization and Intercountry Adoptions of Pets - Sandra Mª López Fernández; Carmen Chicharro; Javier Nieto; Eugenia Carrillo; Eduardo Martínez Manzanares; Fernando Fariñas (Recent Trends in Infectious Diseases, 2023)
Increased temperatures due to climate change may be facilitating that arthropods vectors of zoonotic diseases rapidly colonize new territories. 6472 dogs have been selected to check main Mediterraneum zoonotic vector-borne, two transmitted by fly bites, Leishmaniasis and Dirofilariasis, and tree transmitted by ticks, Ehrlichiosis, Anaplasmosis, and Babesiosis through IFA, ELISA, PCR and microscopy tests and calculate the ratio of this diseases hosts as well the destinations in north of Europe and other countries because these dogs have been adopted out of Spain, the main exported country for dogs to Europe countries, mainly of then are infected with at least one of five vector-borne diseases studied. This represents a risk for Public Health, as it speeds up the creation of new nodes of infected host through facilitated deferred transmmission caused by man.
Keywords: Zoonotic diseases; dirofilariasis; infectious diseases; leishmaniasis; vector borne